Rosemary oil - a remedy for various conditions? - Kmiotek, Weronika; Kwaśniak, Ksenia; Magierska, Agata; Foryś, Angelika; Miłek, Magdalena; Banach, Mariola; Ślusarczyk, Monika; Stawska, Weronika; Kotowicz, Zuzanna; Karuś, Aleksandra (Quality in Sport, 2024)
Introduction and Purpose: The use of rosemary oil has become a new trend in cosmetology and medicine. The purpose of the study is to systematize information on the composition of rosemary oil and its effects on specific health problems. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: “rosemary oil”, “Rosmarinus officinalis”, „rosmarinic acid” and „carnosolin” appropriate configurations. Conclusions: Rosemary oil exhibits a wide range of potential therapeutic and cosmetic applications, making it an extremely versatile and valuable ingredient. Its anti-inflammatory, antioxidant, antibacterial, antifungal, antiviral and anticancer properties confirm its status as a powerful tool in natural medicine. Nonetheless, in order to fully realize its potential, further clinical and experimental research is needed to thoroughly understand its mechanisms of action and to develop effective and safe therapies. In this way, rosemary oil can gain even wider application and become a key element in the treatment of many diseases and in daily health and beauty care.